2018
DOI: 10.1111/jmwh.12927
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Gestational Weight Gain

Abstract: Excessive gestational weight gain (GWG) is associated with an increasing incidence of maternal and neonatal complications, including hypertensive disorders of pregnancy, fetal macrosomia, and increased cesarean birth rates. In the United States, it is recommended that health care providers use an individualized approach to counsel a woman about pregnancy weight gain goals that is based on the woman's initial body mass index (BMI) and to track GWG throughout the pregnancy by evaluating maternal weight at each v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 63 publications
0
69
1
1
Order By: Relevance
“…The observed suboptimal rates of GWG are alarming especially in light of their negative health implications for both the mother and infant. With excessive GWG, mothers tend to have an increased risk of GDM, hypertensive disorders of pregnancy, cesarean section, postpartum weight retention, in addition to a lifelong risk of chronic diseases later on in life for the mother [64][65][66]. On the other hand, women gaining insufficient weight during their pregnancy are at an increased risk of delivering preterm birth and SGA [3,67].…”
Section: Discussionmentioning
confidence: 99%
“…The observed suboptimal rates of GWG are alarming especially in light of their negative health implications for both the mother and infant. With excessive GWG, mothers tend to have an increased risk of GDM, hypertensive disorders of pregnancy, cesarean section, postpartum weight retention, in addition to a lifelong risk of chronic diseases later on in life for the mother [64][65][66]. On the other hand, women gaining insufficient weight during their pregnancy are at an increased risk of delivering preterm birth and SGA [3,67].…”
Section: Discussionmentioning
confidence: 99%
“…3 In this way, it is described that excessive GWG increases the risk of gestational diabetes mellitus, hypertensive syndrome, and cesarean section (C-section). 4 Besides that, excessive GWG has been correlated with postpartum weight retention, obesity, and future metabolic disorders in women. 4 In the children, excessive GWG is associated with macrosomia and increased adiposity in infants, whereas insufficient GWG is associated with lower birthweight and preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…4 Besides that, excessive GWG has been correlated with postpartum weight retention, obesity, and future metabolic disorders in women. 4 In the children, excessive GWG is associated with macrosomia and increased adiposity in infants, whereas insufficient GWG is associated with lower birthweight and preterm birth. 3,4 Despite the adverse effects of excessive GWG, the influence of health-related behaviors on GWG is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Studies have shown that excessive GWG increases the risk of GDM, hypertensive diseases of pregnancy, cesarean section, postpartum weight retention, obesity, and future metabolic disorders. 19,20 Besides that, excessive GWG is correlated with macrosomia and childhood adiposity. 20,21 The maternal psychological state has also been linked with pregnancy outcomes.…”
mentioning
confidence: 99%